Overcoming resistance to cisplatin by inhibition of glutathione S-transferases (GSTs) with ethacraplatin micelles in vitro and in vivo. (November 2017) - Li, Shuyi; Li, Chan; Jin, Shubin; Liu, Juan; Xue, Xiangdong; Eltahan, Ahmed Shaker; Sun, Jiadong; Tan, Jingjie; Dong, Jinchen; Liang, Xing-Jie
Abstract: Platinum-based DNA-adducting agents are used extensively in the clinic for cancer chemotherapy. However, the anti-tumor efficacy of these drugs is severely limited by cisplatin resistance, and this can lead to the failure of chemotherapy. One of cisplatin resistance mechanisms is associated with overexpression of glutathione S-transferases (GSTs), which would accelerate the deactivation of cisplatin and decrease its antitumor efficiency. Nanoscale micelles encapsulating ethacraplatin, a conjugate of cisplatin and ethacrynic acid (an effective GSTs inhibitor), can enhance the accumulation of active cisplatin in cancer cells by inhibiting the activity of GSTs and circumventing deactivation of cisplatin. In vitro and in vivo results provide strong evidence that GSTs inhibitor-modified cisplatin prodrug combined with nanoparticle encapsulation favor high effective platinum accumulation, significantly enhanced antitumor efficacy against cisplatin-resistant cancer and decreased system toxicity. It is believed that these ethacraplatin-loaded micelles have the ability of overcoming resistance of cancers toward cisplatin and will improve the prospects for chemotherapy of cisplatin-resistant cancers in the near future. Graphical abstract: